PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DISERTAI LKS BERBASIS REPRESENTASI GAMBAR DALAM PEMBELAJARAN FISIKA DI KELAS X SMKN 8 JEMBER - Izatul Ismasari; I Ketut Mahardika; Alex Harijanto (FKIP Universitas Jember, 2017)
This research related on the influence of Cooperative Learning model type of Student Achievement Division Team with images representation based LKS in Physics learning at class X SMKN 8 JEMBER. The purpose of this research is: 1) to test the significance of Cooperative Learning model type of Student Achievement Division Team with images representation based LKS in Physics Learning on the activities of students studying physics; and 2) to test the significance of Cooperative Learning model type of Student Achievement Division Team with images representation based LKS in Physics Learning on the cognitive learning physics students. This research is an experimental research, with post-test only control design. This research population is class X at SMKN 8 Jember. Technique to collect the data uses test, observation, documentation, and interviews. Technique to analyze data is Independent-sample T-test (parametric test). The results showed that there is a significant differences between student’s learning physics activities in experimental class and control class with value of Sig.(1-tailed) < 0.05. Meanwhile, the results also showed that there were significant differences between the cognitive learning physics class students experiment and control class with value Sig. (1-tailed)<0.05. The conclusions of the research is : (1) Cooperative Learning model type of Student Achievement Division Team with images representation based LKS influenced significantly on the student’s physics learning activities at class X SMK N 8 Jember, (2) Cooperative Learning model type of Student Achievement Division Team with images representation based LKS influenced significantly on the student’s physics learning cognitive of students at class X SMK N 8 Jember. Keywords: Cooperative Learning model type of Student Achievement Division Team with images representation based LKS, student’s physics learning activities, student’s physics learning cognitive